The Characteristics of Shallow Groundwater Resource in Cangkringan District Sleman Province Special Region of Yogyakarta - Sejati, Sadewa Purba (Media Komunikasi Geografi, 2017)
Cangkringan District (the research site) is one of the districts in Sleman Regency of which spatial function includeswater catchment area. Holding the predicate as a water catchment area, the research area serves as one of the groundwater supply areas for the community living in Sleman Regency. One aspect of integrated water resources management is the water resources information system aspect, in which the geohydrology information system (groundwater) is included. Based on the aspect of water resources management, the study on shallow groundwater characteristics as catchment area in the research site should be conducted. The characteristics of shallow groundwater resources being investigated in this study included the condition and the distribution of groundwater depth, groundwater flow direction, and groundwater electrical conductivity. The primary data were collected on excavation wells of which locationswere determined using systematic random sampling method, by means of making imaginary grids, measuring to 2 km x 2 km. the primary data collected included coordinate data, groundwater depth data, the siteâ€™s altitude, and the groundwater conductivity data. The samples of groundwater electrical conductivity were determined by cluster sampling method, based on the groundwater depth area. The data analysis results demonstrate that shallow groundwater resource in the research site has the following characteristics: the groundwater depth is mostly less than 5 meter, the groundwater flows to the south of the research site, the electric conductivity of the research area has various values, i.e. 187 microS/ cm of the lowest value, and 368 microS/ cm of the highest value.Â Keywords: Cangkringan District, shallow groundwater, groundwater depth, groundwater flow, groundwater electrical conductivity.